The Effect of Adding Milkfish Flour on The Preference Level of Cireng - Muhammad Qobul Raja Dirgantara Giwangkara; Rusky Intan Pratama; Iis Rostini; Emma Rochima (Jurnal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2025)
The enhancement of the nutritional content in Cireng can be achieved by adding milkfish meat flour. This study aims to determine the appropriate amount of milkfish flour to add in the preparation of Cireng to produce the product most preferred by the panelists. The method used was experimental, with four treatments: 0%, 2.5%, 5%, and 7.5% addition of milkfish flour. The parameters observed included preference analysis using a hedonic test to assess appearance, aroma, texture, and taste, as well as proximate analysis and Texture Profile Analyzer (TPA) to evaluate chemical composition and texture characteristics. The results showed that the 5% milkfish flour treatment produced the most preferred Cireng, with the highest average hedonic scores across all sensory attributes: 7.13 for appearance, 7.07 for aroma, 7.80 for texture, and 7.07 for taste. Proximate analysis results showed protein content (3.11%), ash content (0.73%), fat content (0.83%), moisture content (45.36%), and carbohydrate content (48.79%). The TPA results indicated an increase in hardness (1,104.188 gForce) and recovery (0.996%), but a decrease in cohesiveness (0.430%), chewiness (455.576 gForce), gumminess (478.129 gForce), and resilience (0.631%).